Síntese e aplicação de calcogenetos derivados de peptídeos em catálise assimétrica - Schwab, Ricardo Samuel (2010)
In the present work, we have developed a flexible, modular synthetic route for the preparation of new chiral chalcogen peptide derivatives containing sulfur, selenium or oxygen and evaluate their application as catalysts in enantioselective reactions. This modular approach allowed the preparation of a series of chiral compounds with a high structural diversity. In our synthetic route we employed an amide bond formation between Nprotected L-proline and chalcogen amino ester hydrochloride to produce chalcogen peptides in high yields. We used the amino acids L-cysteine and L-methionine as sulfur amino esters, whereas seleno amino ester was prepared from L-serine. O-Bn-L-serine is commercially available. Subsequently, chalcogen peptides were reduced with NaBH4 or Grignard reagents, leading to the formation of N-Boc chalcogenides peptide derivatives in good yields. Deprotection of Boc, under acid condition led to the formation of the target chiral compounds in good yields. Chiral chalgogenides peptides derivatives were then employed as organocatalysts in enantioselective aldol reactions. Several different reaction conditions were screened and enantiomeric excess up to 94 % was achieved for the aldol products. The best result was achieved for organocatalyst derived from L-Bncysteine methyl ester. Extending the application of chalcogenides peptides derivatives which were previously used for aldol reactions, we decided to evaluate the potential of these compounds as catalysts in the asymmetric addition reaction of arylboronic acids to aromatic aldehydes under classical reaction conditions. It was observed that ligand derived from seleno amino ester promoted conveniently this reaction, furnishing the desired products in excellent yields and stereoselectivities up to 91 %.